Workshop Penulisan PTK dan Teknik Submit Artikel Jurnal untuk Guru SD Se-Inhil - Muannif Ridwan; Andriansyah; Indra Muchlis Adnan; Bayu Fajar Susanto (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2021)
The general purpose of this activity is to provide elementary school teachers who are competent in writing scientific papers for teacher professional development. Operationally, the objectives of this activity are: 1) There are skilled teachers who are ready to carry out socialization of various types of teacher professional development; 2) Helping teachers to be able to develop their profession, especially in writing scientific papers resulting from classroom action research (CAR); 3) The development of teachers in doing CAR in the classes they foster; 4) The development of teachers in compiling research reports and scientific journal articles resulting from CAR activities; 5) The publication of articles on the results of CAR activities written by teachers in national scientific journals. To achieve these objectives, training and mentoring methods are used. Material delivery method The training consisted of lecture, question and answer, and discussion methods. Training Results shows that the understanding and mastery of the material on CAR for participants experienced an increase after participating in the training compared to before. At the end of this program activity, 32 teachers successfully completed the task of making classroom action research proposals and were able to create an online submit account for scientific journals.